PEMBERDAYAAN MASYARAKAT UNTUK MENINGKATKAN UMKM DI DESA TEBING LINGGAHARA BARU - Sahat Parulian Sitorus, Sidik Pane (JURNAL BIMA, 2023)
The focus of service journal articles is on the issue of community empowerment through Micro, Small and Medium Enterprises (MSMEs) in improving community welfare. Conditions following the Covid-19 pandemic have resulted in declining MSME productivity, so there is a need for new innovations, especially in the marketing sector. The aim of the service is to find out the results of community empowerment through MSMEs in improving community welfare and the contribution of intern students in community empowerment efforts through MSMEs in improving the welfare of the people of the Cliff Linggahara Baru village in the post-Covid-19 period. The service methodology refers to the SISDAMAS method or a method based on community empowerment. The SISDAMAS method has several cycles consisting of social reflection, social mapping and community organizing, participatory planning and program synergy, program implementation and evaluation monitoring. The results of service in the form of community empowerment through MSMEs in improving community welfare are so that people can live more independently, prosperously and have knowledge about production businesses. The impact of community empowerment is firstly from a social perspective, the community can work together and build strong solidarity. Second, the impact on the economy, namely improving the economic level of society by earning sufficient income. Third, the impact on education is that people gain knowledge and insight after participating in community empowerment. The socialization activities are carried out as an effort to stimulate business actors to continue to be creative and innovate in their respective business fields by prioritizing digital literacy as an important point in facing the digital era like today. In the end, it is hoped that this activity will be beneficial for MSMEs in the culinary sector in the Jatinangor area by involving various parties such as business partners, academics, and local government so that the economy continues to grow and has a good impact on the local community.